Growth of Toxoplasma gondii is inhibited by aryloxyphenoxypropionate herbicides targeting acetyl-CoA carboxylase - Zuther, E. (The National Academy of Sciences, 1999)
Aryloxyphenoxypropionates, inhibitors of the plastid acetyl-CoA carboxylase (ACC) of grasses, also inhibit Toxoplasma gondii ACC. Clodinafop, the most effective of the herbicides tested, inhibits growth of T. gondii in human fibroblasts by 70% at 10 μM in 2 days and effectively eliminates the parasite in 2–4 days at 10–100 μM. Clodinafop is not toxic to the host cell even at much higher concentrations. Parasite growth inhibition by different herbicides is correlated with their ability to inhibit ACC enzyme activity, suggesting that ACC is a target for these agents. Fragments of genes encoding the biotin carboxylase domain of multidomain ACCs of T. gondii, Plasmodium falciparum, Plasmodium knowlesi, and Cryptosporidium parvum were sequenced. One T. gondii ACC (ACC1) amino acid sequence clusters with P. falciparum ACC, P. knowlesi ACC, and the putative Cyclotella cryptica chloroplast ACC. Another sequence (ACC2) clusters with that of C. parvum ACC, probably the cytosolic form.